Design an interactive learning model : using persuasive technology to learn children Arabic alphabets - Alaa H. Abusafia, 1987-; Aryati Bakri, supervisor; Mahadi Bahari; Fakulti Komputeran (2013)
Thesis (Sarjana Sains (Teknologi Maklumat - Pengurusan)) - Universiti Teknologi Malaysia, 2013